Dynamic interactions of Plasmodium spp. with vascular endothelium. Issue 1 (2nd January 2017) - Gillrie, Mark R.; Ho, May
ABSTRACT: Plasmodial species are protozoan parasites that infect erythrocytes. As such, they are in close contact with microvascular endothelium for most of the life cycle in the mammalian host. The host-parasite interactions of this stage of the infection are responsible for the clinical manifestations of the disease that range from a mild febrile illness to severe and frequently fatal syndromes such as cerebral malaria and multi-organ failure. Plasmodium falciparum, the causative agent of the most severe form of malaria, is particularly predisposed to modulating endothelial function through either direct adhesion to endothelial receptor molecules, or by releasing potent host and parasite products that can stimulate endothelial activation and/or disrupt barrier function. In this review, we provide a critical analysis of the current clinical and laboratory evidence for endothelial dysfunction during severe P. falciparum malaria. Future investigations using state-of-the-art technologies such as mass cytometry and organs-on-chips to further delineate parasite-endothelial cell interactions are also discussed.